Implementasi Kebijakan Pengupahan Pada Usaha Mikro Dan Kecil - Akhmad Junaedi (Pusat Penelitian dan Pengembangan Ketenagakerjaan Kementerian Ketenagakerjaan Republik Indonesia, 2018)
In the national economy wages have a very strategic position both for workers, employers and for governments, each of which has different interests. Therefore, the government is instrumental to maintain the balance between the interests of employers and the interests of workers/laborers. The government is also obliged to create industrial relations between the two sides in a harmonious and equitable way to maintain business stability and increase productivity. Wages for entrepreneurs as production costs so often are subjected to emphasis for efficiency reasons. In an effort to anticipate these conditions, the government has issued legislation concerning wages including Government Regulation No. 8 of 1981 on the Protection of Wages,Regulation of the Minister of Manpower and Transmigration No. Per-17/Men/1999 on Minimum Wages, Law number. 13 of 2003 on Manpower. Because of the stronger demands of workers/laborers on the components of decent living needs, in order to ensure business sustainability, investment climate and guarantee of wage system, the government issued PP No.78 of 2015 on wages. Although micro and small enterprises contribute greatly to job creation and gross domestic product, they are constrained by financial constraints, management, places of business, and marketing. On the other hand, there is a policy of minimum wage that must be implemented. However, in the implementation of these provisions are very difficult to meet by the perpetrators of micro and small businesses. In relation thereto, the minimum wage policy/condition can not be applied at all business scales. At the micro and small scale enterprises can not be forced to pay the wage of workers/laborers in accordance with the provisions of the minimum wage that has been set.